Noninvasive Monitoring of Allogeneic Stem Cell Delivery with Dual-Modality Imaging-Visible Microcapsules in a Rabbit Model of Peripheral Arterial Disease - Yingli Fu; Clifford R. Weiss; Dorota A. Kedziorek; Yibin Xie; Ellen Tully; Steven M. Shea; Meiyappan Solaiyappan; Tina Ehtiati; Kathleen Gabrielson; Frank H. Wacker; Jeff W. M. Bulte; Dara L. Kraitchman (Stem Cells International)
Stem cell therapies, although promising for treating peripheral arterial disease (PAD), often suffer from low engraftment rates and the inability to confirm the delivery success and track cell distribution and engraftment. Stem cell microencapsulation combined with imaging contrast agents may provide a means to simultaneously enhance cell survival and enable cell tracking with noninvasive imaging. Here, we have evaluated a novel MRI- and X-ray-visible microcapsule formulation for allogeneic mesenchymal stem cell (MSC) delivery and tracking in a large animal model. Bone marrow-derived MSCs from male New Zealand White rabbits were encapsulated using a modified cell encapsulation method to incorporate a dual-modality imaging contrast agent, perfluorooctyl bromide (PFOB). PFOB microcapsules (PFOBCaps) were then transplanted into the medial thigh of normal or PAD female rabbits. In vitro MSC viability remained high (79±5% at 4 weeks of postencapsulation), and as few as two and ten PFOBCaps could be detected in phantoms using clinical C-arm CT and 19F MRI, respectively. Successful injections of PFOBCaps in the medial thigh of normal (n=15) and PAD (n=16) rabbits were demonstrated on C-arm CT at 1-14 days of postinjection. Using 19F MRI, transplanted PFOBCaps were clearly identified as “hot spots” and showed one-to-one correspondence to the radiopacities on C-arm CT. Concordance of 19F MRI and C-arm CT locations of PFOBCaps with postmortem locations was high (95%). Immunohistological analysis revealed high MSC survival in PFOBCaps (>56%) two weeks after transplantation while naked MSCs were no longer viable beyond three days after delivery. These findings demonstrate that PFOBCaps could maintain cell viability even in the ischemic tissue and provide a means to monitor cell delivery and track engraftment using clinical noninvasive imaging systems.